Effect of a single dose of i.v. ondansetron on QTc interval in emergency department patients. (1st March 2018) - Li, Kai; Vo, Kathy; Lee, Byron K.; Addo, Newton; Coralic, Zlatan
Abstract : Purpose: Results of a study to determine whether i.v. administration of a single dose of 4 mg of ondansetron was associated with QT interval prolongation in emergency department (ED) patients are reported. Methods: In a prospective observational study conducted at an urban academic medical center ED, a convenience sample of adult ED patients treated with ondansetron 4 mg i.v. were enrolled. A 12-lead electrocardiogram (ECG) was obtained immediately before and 5 minutes after ondansetron administration. Measurements of heart rate–corrected QT interval (QTc measurements) provided by ECG machines were evaluated. An electrophysiologist analyzed all ECGs for adverse electrical events and verified the accuracy of QTc values. The primary objective was to measure the QTc change from baseline after ondansetron administration. The secondary objective was to describe adverse electrical cardiac events. Interactions between ondansetron and patients' home medications or ED-provided medications were analyzed. Results: Among patients included in the data analysis ( n = 20), ondansetron administration was associated with a mean QTc increase of 16.2 msec (95% confidence interval, 4.2–28.2 msec; p = 0.01) and a median increase of 12 msec (interquartile range, 5.5–18.0 msec; p < 0.01). One patient had a significant cardiac event (pulseless electrical activity) that was likely unrelated to ondansetron use. The home medications of 9 patients (42.9%) were deemed to pose a risk of torsades de pointes, and 17 major QT-prolonging drug–drug interactions were identified. Conclusion: Significant QTc prolongation occurred in ED patients receiving a single 4-mg i.v. dose of ondansetron. None of the patients had an ondansetron-related cardiac adverse event.